The role of yoghurt consumption in the management of type II diabetes. Issue 12 (19th November 2020) - Yanni, Amalia E.; Kartsioti, Kleio; Karathanos, Vaios T.
Abstract : Enrichment of yoghurt with specific ingrdients beneficially affects the management of Type II Diabetes Mellitus (DMII). Abstract : Enrichment of yoghurt with specific ingrdients beneficially affects the management of Type II Diabetes Mellitus (DMII). As far as the role of yoghurt in the management of DMII is concerned, the limited number of randomized clinical trials (RCTs) which have been conducted suggest that daily intake of yoghurt enriched with vitamin D and/or calcium as well as probiotics positively influences glycemic regulation and may contribute to more effective control of the disease. It is argued that the various ingredients which are already contained in the complex matrix of food, such as bioactive peptides, calcium, B-complex vitamins and beneficial microbes, as well as the fact that it can be used as a vehicle for the inclusion of other effective ingredients can have an impact on the metabolic control of diabetic patients. The aim of this review is to present the RCTs which have been conducted in the last decade in patients with DMII in an attempt to highlight the positive effects of yoghurt in the management of the disease.